Design of intelligent hybrid energy ambulatory surgical center ship in efficient way - Tawheed Hasan,; Shahrizan Jamaludin,; W.B. Wan Nik, (Penerbit Universiti Kebangsaan Malaysia, 2024)
An Ambulatory Surgical Center (ASC), also known as an outpatient surgery center, is a medical facility that provides same-day surgical procedures to patients who do not require an overnight stay in a hospital. ASCs are equipped with state-of-the-art medical equipment and staffed by highly trained healthcare professionals, including surgeons, anaesthesiologists and nurses. There are many areas along the river where people do not have easy access to any surgery. They have to go far to get this service, for which they do not even take the service. This research is for them. This research will ensure their basic medical services. The contribution of this research, this world-class surgical ship goes to ensure the basic medical needs of poor people in remote areas where good healthcare is not available. Another great contribution that will surprise the world is that no conventional fuel is needed to ensure this healthcare service. So undoubtedly this research has a great contribution in the global energy crisis. To ensure efficient ambulatory surgical center (ASC) ship, conducting site assessment, sizing the hybrid system appropriately, selecting the right components, improving hybrid energy system design, implement intelligent system is important. And these are the scope of our research. A detailed analysis of all possible aspects has shown that using intelligent hybrid energy ships instead of conventional ships improves the quality of service. Long lasting service is achieved with low energy consumption, sustainability and no pollution even without compromising performance. In this research details of ASC will be critically discussed.